The rise of artificial intelligence reading of chest X-rays for enhanced TB diagnosis and elimination - Geric, Coralie; Qin, Z. Z.; Denkinger, Claudia M.; Kik, S. V.; Marais, B.; Anjos, A.; David, P-M.; Ahmad Khan, F.; Trajman, A. (The international journal of tuberculosis and lung disease, 2023)
We provide an overview of the latest evidence on computer-aided detection (CAD) software for automated interpretation of chest radiographs (CXRs) for TB detection. CAD is a useful tool that can assist in rapid and consistent CXR interpretation for TB. ...
Das PDF enthält zusätzlich eine Zusammensetzung in französischer Sprache
Gesehen am 21.11.2023